Data from: Development of the Combined Assessment of Risk Encountered in Surgery (CARES) surgical risk calculator for prediction of post-surgical mortality and need for intensive care unit admission risk ? a single-centre retrospective study - Diana Xin Hui Chan (2018)
doi:10.5061/dryad.v142481